Validation of OpenCap on lower extremity kinematics during functional tasks - Svetek, A.; Morgan, K.; Burland, J.; Glaviano, N. R. (Journal of Biomechanics, 2025)
Marker-based motion capture is a fundamental tool in biomechanical analysis, yet comes with major constraints such as time, cost and accessibility. This study aimed to validate the use of OpenCap, a free, markerless motion capture system compared to a marker-based motion capture system to measure lower extremity kinematics during functional tasks. 20 individuals from an athletic population (18 females, 2 males) performed two gait trials (walking, running) and three functional tasks (double leg squat, countermovement jump, jump-landing). Lower extremity peak joint kinematics were collected simultaneously using Vicon and OpenCap to assess the validity of markerless motion capture. Strong agreements were observed in the frontal hip plane joint kinematics across all tasks with root mean squared errors below 6°. Moderate agreements were observed in the sagittal knee plane joint kinematics (4-10°) and there was a weak agreement in the gait trials of the sagittal hip measures (>10°). The results from the study indicate the need for further research on the use of OpenCap in clinical settings. The findings align with previous studies with similar agreements observed in the frontal hip and sagittal knee measures. Validating the use of an open-source motion capture software could provide clinicians and researchers an accessible tool for in depth biomechanical assessments.